Os elementos de Iansã como possibilidade para criação cênica - Moraes, Daniela Beny Polito (2017)
The present research of master "Iansan elements like possibility to scenic creation", under the guidance of Professor Teodora de Araújo Alves aims to understand the traffic Iansan dance and its mythical elements between Candomblé, Afoxé, the lab and the theatre, in order to elaborate a methodological proposal for expansion of the body of repertoire interpreters-creators. Because it is a study that involves subjectivity of individuals, the related to this research, the same looks at the basis of Phenomenology by Merleau-Ponty to treat the body as a way of being in the world. To reflect on the fields of Performance that makes up this investigation, seek dialogue with the anthropology of Performance based on studies of Richard Schechner and Victor Turner, the Theatrical Anthropology proposed by Eugenio Barba and the studies in afro-amerindians Performances developed by Zeca Ligiéro. This investigation developed by the Afoxé Oju Omim Omorewá (Maceió/AL), noting the saída-de-orixá of Ialorixá Nany Moreno – Coordinator of Afoxé – and practical-creative experiments by the Coletivo Cores (Natal/RN).